Principal Paternalistic Leadership Style, Teachers Commitment and Productivity in Public Schools in Ilorin West Local Government Area of Kwara State (Kwasu International Journal of Educational Management and Leadership, 2026)
The principal leads by organizing all jobs in the school. Teacher productivity in the school is determined by internal and external factors. Leadership style that allows principals to create positive school cultures and increase teachers' productivity has been the subject of discussion. Therefore, the study investigated mediating effect of teachers’ commitment on the relationship between paternalistic leadership styles of school principals and teachers’ productivity in Public Schools in Ilorin West Local Government. The study used descriptive research design to obtain the data from respondents. Stratified random sampling technique was used to select 300 respondents. Three instruments were designed tagged paternalistic leadership, teacher commitment, and teacher productivity. Structural Equation Modeling was used to analyse the hypotheses formulated. The findings revealed that paternalistic leadership style had significant relationship with teacher productivity where regression weight indicated β=.859 and significant at p<0.05. The finding further found that paternalistic leadership style had significant relationship with teacher commitment with regression weight of β=.949 and significant at p<0.05. Also, the finding revealed that teacher commitment had significant relationship with teacher productivity where regression weight indicates β=.949, p<0.005. Finally, the finding reported that teacher commitment mediates the relationship between paternalistic leader style and teachers’ productivity with partial mediator. The findings concluded that principals’ paternalistic leadership is the predictor of teacher productivity. Based on the findings, it was suggested principals should practices paternalistic leadership in the school so as to enhance teacher productivity.